1996
DOI: 10.1063/1.472385
|View full text |Cite
|
Sign up to set email alerts
|

Solvent dynamics: Modified Rice–Ramsperger–Kassel–Marcus theory. II. Vibrationally assisted case

Abstract: Expressions are given for a solvent dynamics-modified Rice-Ramsperger-Kassel-Marcus ͑RRKM͒ theory for clusters. The role of vibrational assistance across the transition state region is included. The usual differential equation for motion along the slow coordinate X in constant temperature systems is modified so as to apply to microcanonical systems. A negative entropy term, ϪS v (X), replaces the (1/T)‫ץ‬U/‫ץ‬X or (1/T)‫ץ‬G/‫ץ‬X which appears in canonical systems. Expressions are obtained for the RRKM-type rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…9.14), where the decay is nonexponential even when the correlation function is exponential. Similar applications of the effective sink approximation can be found in the literature [311][312][313][314][315].…”
Section: Effective Sink Approximationmentioning
confidence: 76%
“…9.14), where the decay is nonexponential even when the correlation function is exponential. Similar applications of the effective sink approximation can be found in the literature [311][312][313][314][315].…”
Section: Effective Sink Approximationmentioning
confidence: 76%
“…They found that classical motions associated with the bending dynamics exhibit a transition from normal modes to local modes as the excitation energy increases. 10,11 Similar transitions have been explored in the broader context of intramolecular vibrational relaxation, isomerization, and energy localization by Heller et al [12][13][14][15][16][17][18][19] A question in these studies is the manifestation of classical chaos in quantum dynamics and possible spectroscopic measurements. 20,21 Wilkie and Brumer recently developed a quantum-classical correspondence via Liouville dynamics for both integrable and chaotic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral density of the bath was in the Ohmic form 21) with the cut off frequency w, well below the system oscillation frequency wo. The latter means the absence of the energy relaxation contribution to the process of dephasing.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Heisenberg's correspondence relation and its generalization to non-linear response functions provide the theoretical basis for such mapping. (2) The dynamics of polyatomic molecules has stimulated topics such as intramolecular vibrational relaxation, isomerization, and energy localization [14,15,16,17,18,19,20,21].…”
Section: Introduction 11 Motivationmentioning
confidence: 99%